Plan de negocios para la producción y comercialización de shampoo con ingredientes biodegradables - Yépez Jijón, Pablo Sebastián (2016)
The government of Ecuador seeks to develop national productive matrix, this is the reason why they have been implementing incentives and benefits for companies that produce goods made in the country, to thereby be able to develop products that are competitive enough to Ecuadorian consumers so they do not need to buy foreign products. In addition, consumption of cosmetic products, including shampoo, has increased given that people spend a larger part of their income for personal hygiene products for their families. This is how the idea to manufacture and market a shampoo with biodegradable ingredients that has 4 benefits in 1 in a doypack presentation, making it a more economical product for men and women aged 20 to 30 years of Quito who are interested in maintaining a proper care of their hair. The overall marketing strategy is to focus on a niche market and position itself in the market by offering a product with several benefits with a lower price compared to the competition. The amount of investment needed is USD 40,600 to carry out this project, which will be financed with 60% own capital and 40% debt, with 11,50% interest. It was determined that the project is viable by performing the financial plan where a NPV and IRR 17,082.42 was obtained and 30.19% respectively.